SR/BA IN BARITE: A PROXY OF BARITE PRESERVATION IN MARINE SEDIMENTS? - Van Beek P.; Reyss J.-L.; Bonte P.; Schmidt S. (My University, 2003)
The observation by Bertram and Cowen [J. Mar. Res. 55 (1997) 577–593] that the strontium content of marine barite decreased from the water column to the deep-sea floor suggested that the Sr/Ba ratio in barite was sensitive to barite dissolution. Following this observation, we have investigated the potential of using the Sr/Ba ratio in barite as a proxy of barite preservation by separating barite crystals from sediment cores collected at different water depths in the equatorial Pacific and in the Southern Ocean. Our investigations do not reveal significant downcore variations in the Sr/Ba ratios during the Holocene period in the two basins and up to a few hundred thousand years in the equatorial Pacific. However, a comparison of the mean Sr/Ba ratios in individual cores suggests that the Sr/Ba ratios in barite decrease with increasing water depth, a feature that could be related to dissolution of barite crystals during settling to the deep-sea floor and/or at the sediment–water interface. If confirmed, the Sr/Ba ratios in barite could be used to infer the intensity of barite dissolution and the state of preservation of barite crystals in sediments. Such information could be employed usefully in paleoproductivity reconstructions for the purpose of distinguishing between productivity and dissolution signals affecting barite distributions in marine sediments.
Keywords: barite; strontium; dissolution